Perancangan Sistem Pakar Diagnosa Penyakit Mata Menggunakan Metode Certainty Factor - Monica Oktavianti; Feri Candra; Zulharman Zulharman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The development of computer technology helps people to solve their problems, for example is Artificial Intelligence. The smarter the system and information handled, the more active role played by computers and there has been an increase in people interest using computers for artificial intelligence. One of the areas of artificial intelligence engineering that is quite attractive is expert systems. Expert system is a computer that designed to copy the expert knowledge. Expert system can be implemented in the hospital. clinics etc. Expert system in this research is using certainty factor method for diagnosis of eye diseases. This method helps people and provide solutions to the symptoms experienced by the user. The results of this study are the diagnosis of eye diseases, the information of the diseases, solutions and early treatment methods for eye diseases. By using black box testing, an accuracy of 94.4% is obtained.Keywords : Expert System, Eye disease, Certainty Factor